2023
DOI: 10.1186/s42523-023-00270-8
|View full text |Cite
|
Sign up to set email alerts
|

Compound Bacillus alleviates diarrhea by regulating gut microbes, metabolites, and inflammatory responses in pet cats

Fei Wang,
Xiaoying Mei,
Qi Wang
et al.

Abstract: Background Pet cats frequently have diarrhea in their daily life. Bacillus has a protective role that has crucial beneficial functions on intestinal homeostasis. The aim of this research was to investigate the effects of the compound Bacillus on the prevention of diarrhea, microbiota and metabolism in pet cats. A total of 20 pet cats (1–2 years old, 3.91 ± 0.92 kg) were randomly divided into two groups and fed with a basal diet (Control group), or a basal diet supplemented with 3 × 109 CFU/kg c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Lee et al [ 13 ] found that Bacillus licheniformis fermentation products, previously used as additives in poultry and pig feed, improved fecal consistency in a few cats and significantly increased the numbers of Blautia spp., Ruminococcus torques , and Ruminococcus gnavus in feces. Wang et al [ 14 ] discovered that probiotics ( Bacillus amyloliquefaciens SC06 and Bacillus subtilis B10) significantly reduced the incidences of soft stools and diarrhea in pet cats, markedly increased the numbers of Patescibacter and Plectosphaerella in cat feces, and decreased the abundances of Firmicutes , Gemmatimonadetes , Ruminococcaceae , Ascochytahe , and Saccharomyces . The probiotic SLAB51™, comprising several Lactobacilli , Bifidobacteria, and Streptococcus species, significantly increased the numbers of Lactobacillus spp.…”
Section: Probiotics and General Intestinal Healthmentioning
confidence: 99%
“…Lee et al [ 13 ] found that Bacillus licheniformis fermentation products, previously used as additives in poultry and pig feed, improved fecal consistency in a few cats and significantly increased the numbers of Blautia spp., Ruminococcus torques , and Ruminococcus gnavus in feces. Wang et al [ 14 ] discovered that probiotics ( Bacillus amyloliquefaciens SC06 and Bacillus subtilis B10) significantly reduced the incidences of soft stools and diarrhea in pet cats, markedly increased the numbers of Patescibacter and Plectosphaerella in cat feces, and decreased the abundances of Firmicutes , Gemmatimonadetes , Ruminococcaceae , Ascochytahe , and Saccharomyces . The probiotic SLAB51™, comprising several Lactobacilli , Bifidobacteria, and Streptococcus species, significantly increased the numbers of Lactobacillus spp.…”
Section: Probiotics and General Intestinal Healthmentioning
confidence: 99%